Improper patient positioning incidence for panoramic radiographic imaging of pediatric patients: Retrospective study - Ozdil Nihal Yetimoglu; Oflezer Ozlem; Gokkaya Berna; Bahadir Hakan; Orhan Kaan (Balkan Stomatological Society, 2022)
Background/Aim: Improper positioning of the patient reduces the diagnostic quality of panoramic radiographs. It is important to perfect the panoramic patient positioning technique to avoid unnecessary repeat exposures especially in pediatric patients. In this study, pediatric patient sample of records collected from an oral and dental health center were analyzed to determine the relative incidence of positioning errors of panoramic radiographs. Material and Methods: 3788 (1928 girls, 1860 boys) digital panoramic radiographs obtained from the stored data in the system were selected randomly. The radiographs were evaluated by two radiology specialists, by recording separately. The positioning errors of the images were categorized into ten groups: the chin tipped high, chin tipped low, a slumped position, the patient positioned forward, the patient positioned backward, failure to position the tongue against the palate, patient movement during exposure, the head tilted, and the head turned to one side. The results were statistically analyzed for positioning errors according to age and gender. Results: In 3788 radiographs, 2138 (56.4%) were error-free and 1650 (43.6%) were present with positioning errors. In the improper images, a single positional error was present in 1379 (83.6%); two positional errors were present in 248 (15%) and three or more positional errors in 23 (1.4%). The most common error observed was the tongue not being in contact with the hard palate (32.1%). On the other hand, the least common experienced error was patient movement during exposure (2.0%). Conclusions: The positioning errors of panoramic radiographs were common in the sample group of this study. Careful patient positioning can play a significant role in improving the radiographic quality and reducing the number of retakes.